STRUCTURAL CHANGE, ECONOMIC GROWTH, AND EMPLOYMENT OPPORTUNITIES IN INDONESIA; A Simultaneous Approach - Tarmidi, Didi; Rays Pattilouw, Djufri; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze the relationship between structural change, economic growth, and employment in Indonesia. The analytical method uses a dissimultaneous regression model consisting of three equations where economic growth, structural change, and employment are treated as endogenous variables and include three (3) exogenous variables, namely investment, wage, and education. From the identification test, it is known that the equation of employment is exactly identified and then estimated using the indirect least squares (ILS) method, while 2 other sareover-identified equations are then estimated using a two-stage least squares (TSLS) method. The results showed that: 1) Economic growth is positively and significantly influenced by employment and investment; 2) Employment is positively and significantly influenced by economic growth and structural change, while the wage rate has a negative effect; 3) structural change is positively and significantly influenced by economic growth and the advancement of education. Important recommendations of these findings are: 1) expansion of employment should be more focused on efforts to encourage productive investments with labor-intensive technologies; 2) increased investments must be accompanied by improvement of the level of education and improving the quality of labor; 3) the process of structural change must be maintained in the direction of employment transformation through the development of labor-intensive industrial and service sectors.